2012
DOI: 10.1111/j.2047-6310.2012.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of physical activity and sedentary time with weight and weight status among 10‐ to 12‐year‐old boys and girls in Europe: a cluster analysis within the ENERGY project

Abstract: Engagement in more MVPA and less sedentary time is associated with a more favourable weight status among 10- to 12-year-old girls. Among boys, MVPA seems most important for weight status, while sedentary time appears to be less relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
51
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 48 publications
12
51
2
2
Order By: Relevance
“…All studies were published in 2008 or later, with participants ranging from 4-18 years of age (the mean age was between 5.0 and 17.9 years). Of the 14 included studies, 10 reported on adiposity (Aggio et al 2015;Chaput et al 2014b;De Bourdeaudhuij et al 2013;Ekelund et al 2012;Herman et al 2014;Hjorth et al 2014b;Katzmarzyk et al 2015;Laurson et al 2008Laurson et al , 2014Loprinzi et al 2015), 3 on cardiometabolic risk factors (de Moraes et al 2013;Ekelund et al 2012;Hjorth et al 2014a), and 3 on cardiorespiratory or musculoskeletal fitness (Aggio et al 2015;Martinez-Gomez et al 2011;Santos et al 2014). Two papers (Aggio et al 2015;Ekelund et al 2012) reported on more than 1 indicator.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies were published in 2008 or later, with participants ranging from 4-18 years of age (the mean age was between 5.0 and 17.9 years). Of the 14 included studies, 10 reported on adiposity (Aggio et al 2015;Chaput et al 2014b;De Bourdeaudhuij et al 2013;Ekelund et al 2012;Herman et al 2014;Hjorth et al 2014b;Katzmarzyk et al 2015;Laurson et al 2008Laurson et al , 2014Loprinzi et al 2015), 3 on cardiometabolic risk factors (de Moraes et al 2013;Ekelund et al 2012;Hjorth et al 2014a), and 3 on cardiorespiratory or musculoskeletal fitness (Aggio et al 2015;Martinez-Gomez et al 2011;Santos et al 2014). Two papers (Aggio et al 2015;Ekelund et al 2012) reported on more than 1 indicator.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…SB was objectively measured using accelerometers in 12 studies (Aggio et al 2015;Chaput et al 2014b;De Bourdeaudhuij et al 2013;de Moraes et al 2013;Ekelund et al 2012;Martinez-Gomez et al 2011;Herman et al 2014;Hjorth et al 2014aHjorth et al , 2014bKatzmarzyk et al 2015;Loprinzi et al 2015;Santos et al 2014), and self-reported in 4 studies (Herman et al 2014;Hjorth et al 2014b;Laurson et al 2008Laurson et al , 2014. Two studies (Herman et al 2014;Hjorth et al 2014b) included both self-reported and objective measures of SB.…”
Section: Measurement Of Movement Behavioursmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, mothers of lower education have been previously reported not to set any rules to control the time their young children are engaged in screenrelated activities (e.g., TV watching) because this is usually a convenient way of babysitting or calming down their children [30]. Increased screen time, however, is among the EBRBs that have been most strongly associated with overweight and/or obesity in various life stages [27,31].…”
Section: Tablementioning
confidence: 99%